'Pseudo-dominant' inheritance in Friedreich's ataxia. Issue 4 (August 1981) - Harding, A E; Zilkha, K J
Abstract : A family is described in which Friedreich's ataxia occurred in two generations. It is proposed that this resulted from a homozygote-heterozygote mating. The heterozygote frequency for the Friedreich's ataxia gene is in the order of 1 in 110, so the likelihood of the disease developing in an individual child of a patient is 1 in 220. This risk is probably higher than that often assumed when counselling patients with this disorder.